2017
DOI: 10.1016/j.conctc.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

TelePain: Primary care chronic pain management through weekly didactic and case‐based telementoring

Abstract: Chronic pain is a significant problem among military personnel and a priority of the military health system. The U.S. Army Surgeon General's Pain Management Task Force recommends using telehealth capabilities to enhance pain management. This article describes the development and evaluation of a telehealth intervention (TelePain) designed to improve access to pain specialist consultation in the military health system. The study uses a wait-list cluster controlled clinical trial to test: 1) effectiveness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is grounded in adult learning principles and includes aspects of case‐based learning, didactic education and interprofessional consultation . Pilot research on ECHO for topics such as pain management and hepatitis C has identified measurable increases in provider self‐efficacy and knowledge, and one study found an association between New Mexico's SUD ECHO implementation and number of per‐capita physicians with the DATA‐2000 buprenorphine waiver . Recently, the New Mexico SUD ECHO was included in a scoping review of models for integrating treatment of OUD into primary care settings .…”
mentioning
confidence: 99%
“…It is grounded in adult learning principles and includes aspects of case‐based learning, didactic education and interprofessional consultation . Pilot research on ECHO for topics such as pain management and hepatitis C has identified measurable increases in provider self‐efficacy and knowledge, and one study found an association between New Mexico's SUD ECHO implementation and number of per‐capita physicians with the DATA‐2000 buprenorphine waiver . Recently, the New Mexico SUD ECHO was included in a scoping review of models for integrating treatment of OUD into primary care settings .…”
mentioning
confidence: 99%
“… 78 Integrated care models with primary care using pain management services via telehealth have been described but not studied. 79 , 80 , 81 In one study, military PCPs were given access to video consults with pain management specialists as well as an online pain management curriculum. Patients were asked to assess their pain at various intervals up until 8 weeks after their visit with a PCP.…”
Section: Telehealth Modalitiesmentioning
confidence: 99%
“…Data are still pending from this study. 79 In a qualitative assessment, 48 e-consults to pain management specialists from PCPs were assessed for the types of patients who were most likely to be referred via this form of consultation. The most common patient diagnoses included chronic pain patients with mental health diagnoses, substance dependence, and social complexity.…”
Section: Telehealth Modalitiesmentioning
confidence: 99%